EVALUATION OF SUSTAINABLE SUPPLY CHAIN STRATEGY OF BANK DEPOSITS IN RUSSIA AND EU COUNTRIES IN CRISIS CONDITIONS - Grinko, Elena L. (International Journal of Supply Chain Management, 2019)
Abstract - This article analyzes the impact of economic instability resulting from the global crisis of the dynamics of bank deposits in the banks. The sustainable supply chain strategy is developed for evaluation bank performance. The behavioral nature of the changes in the stability of time deposits and demand deposits in banks due to the crisis phenomena, verified as consequences of the global crisis, has been examined. Results demonstrated the significant efficiency of supply chain in bank and economic situation.